The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41467-021-27595-9
|View full text |Cite
|
Sign up to set email alerts
|

Robust and durable serological response following pediatric SARS-CoV-2 infection

Abstract: The quality and persistence of children’s humoral immune response following SARS-CoV-2 infection remains largely unknown but will be crucial to guide pediatric SARS-CoV-2 vaccination programs. Here, we examine 548 children and 717 adults within 328 households with at least one member with a previous laboratory-confirmed SARS-CoV-2 infection. We assess serological response at 3–4 months and 11–12 months after infection using a bead-based multiplex immunoassay for 23 human coronavirus antigens including SARS-CoV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
62
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 34 publications
16
62
2
Order By: Relevance
“…Having determined that mRNA vaccines produce a significantly higher proportion of RBD and S1 antibodies, we next investigated their ACE2 binding inhibition as these antigens are predominantly responsible for antibody-mediated virus neutralization ( 12 , 13 ). For this, we used a previously published ACE2-RBD competition assay ( 22 , 29 , 30 ), which detects neutralizing antibody activity only and is comparable to classical viral neutralization assays ( 24 , 29 ). As expected, homologous mRNA vaccination resulted in higher ACE2 binding inhibition than homologous vector-based vaccination (median ACE2 binding inhibition mRNA-1273 93.1%, BNT162b2 80.1%, AZD1222 38.5%, Ad26.CoV2.S 3.3%, Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having determined that mRNA vaccines produce a significantly higher proportion of RBD and S1 antibodies, we next investigated their ACE2 binding inhibition as these antigens are predominantly responsible for antibody-mediated virus neutralization ( 12 , 13 ). For this, we used a previously published ACE2-RBD competition assay ( 22 , 29 , 30 ), which detects neutralizing antibody activity only and is comparable to classical viral neutralization assays ( 24 , 29 ). As expected, homologous mRNA vaccination resulted in higher ACE2 binding inhibition than homologous vector-based vaccination (median ACE2 binding inhibition mRNA-1273 93.1%, BNT162b2 80.1%, AZD1222 38.5%, Ad26.CoV2.S 3.3%, Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Spike, Receptor Binding Domain (RBD), S1 domain, S2 domain and nucleocapsid) and the endemic coronaviruses (OC43, HKU1, NL63 and 229E). While samples were processed using an automated platform on a Beckman Coulter i7 pipetting robot as previously described ( 30 ) with minor modifications, all sample and reagent dilutions were already established and verified as part of the initial MULTICOV-AB technical assay validation process which is detailed in ( 28 ). Briefly, samples were thawed at room temperature, vortexed and then centrifuged at 2000 g for 3 mins to pellet any cell debris within the sample.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, children maintained antibody and cellular responses longer than 12 months, while adults showed a waning immune response at 6 months (Dowell et al ., 2022 ). German immunologists who analysed the immune response in 550 children and 700 adults observed no significant difference in antibody response between symptomatic and asymptomatic infections both for children and adults (Renk et al ., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…One mechanism thought to mediate protection is the development of neutralizing antibodies (nAb) to SARS-CoV-2, which have been shown to be predictive of protection from symptomatic COVID-19 infection 2 , and are often used as a correlate of protective immunity to SARS-CoV-2. While there are numerous studies of humoral immunity in adults, studies in children are limited, with conflicting results [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . Two recent and large studies in children demonstrated that children develop neutralizing antibodies at similar levels and with similar duration to those seen adults after infection 8,12 .…”
Section: Introductionmentioning
confidence: 99%
“…While there are numerous studies of humoral immunity in adults, studies in children are limited, with conflicting results [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . Two recent and large studies in children demonstrated that children develop neutralizing antibodies at similar levels and with similar duration to those seen adults after infection 8,12 . Yet in earlier studies, children with severe or mild to severe COVID-19 had lower nAb levels and duration than adults 4,11,17 .…”
Section: Introductionmentioning
confidence: 99%